Climate Services for Resilient Development in South Asia: Semi-annual Report, January to June 2019 - Krupnik, Timothy J.; Hussain, Ghulam; Montes, Carlos; Amjath-Babu, Tharayil Shereef; Schulthess, Urs C.; Siddiquee Iqbal, Ansar A.; Khan, Shahidul Haque; Salam, Moin; Khanam, Fahmida; Kamal, Mustafa; Pilat, Anne-Laure; Mason, Simon J.; et al. (2019)
Recognizing that strengthening the climate resilience of developing nations can be achieved through relevant climate data and scientific insights, the partnership Climate Services for Resilient Development (CSRD) is aligned with the Global Framework for Climate Services and brings together climate science, data streams, and decision support tools, while also facilitating training for decision-makers on climate services. CSRD in South Asia is supported by the United States Government and with a steering consortium committee comprised of the UK Government Department for International Development (DFID), UK Meteorological Office, Environmental Systems Research Institute (ESRI), Google, the Inter-American Development Bank (IADB), the Asian Development Bank (ADB), and the American Red Cross (ARC). In South Asia, CSRD activities are led by the International Maize and Wheat Improvement Center (CIMMYT). This report details activities of the CSRD project in South Asia during the first half of 2019.